COMPARATIVE ANALYSIS OF THE TREATMENT OF THE EOSINOPHILIC GRANULOMA WITH VERTEBRAL INVOLVEMENT USING ORTHOPEDIC CORSET AND SURGICAL OPERATION - A. I. Snetkov; S. V. Kolesov; A. P. Frantov; S. Yu. Batrakov; S. A. Kudryakov; R. M. Efendiev; M. L. Sazhnev (Travmatologiâ i Ortopediâ Rossii, 2016)
The results of treatment of 72 patients with pathological fracture of vertebra bodies against eosinophilic granuloma a spine are analysed. Orthopedic corset technologies are used in treatment of 42 patients, surgical treatment was applied. Orthopedic corset may be used in patients with eosinophilic granuloma of backbone. This method of treatment was used in a case of the absence of spine secondary deformations and neurologic semiology. Orthopedic corset treatment is associated with long immobilization on the average within 1,5-2 years and never leads to a complete recovery of the damaged spine. Surgical treatment consists in use only at loss of height of a body to 30-40%, when destruction of spine more severe it is necessary to use operative treatment in two stages. Absolute indications to surgical treatment are the neurologic deficit and secondary deformations of a spine. Surgical treatment allows to reduce terms of treatment till 3-4 months and quickly to return the patient to an active life.